ANALISIS HASIL UJI TERAP ALAT PENGHEMAT BBM ELECTRIC FUEL TREATMENT PADA ENGINE DIESEL GENSET 35 KVA DENGAN BEBAN STATIS - Hariyadi, -; Sugiono, -; Fakhrurroja, Hanif; Tanu, Edy (LIPI Press, 2011)
This paper describe fi eld test results analysis for fuel saving tool called Electic Fuel Treatment (EFT) on diesel engine generator set 35 KVA with static load. Field test on diesel engine generator set was performed with a variety of confi gurations EFT in series or parallel to get the best fuel effi ciency. Methods of analysis done bythe operational technical tests by comparing the results of testing before and after installation of EFT. Field test results are a form of EFT confi gurations that is ideal to obtain fuel effi ciency on average of 6.58% at 60% load and exhaust emission reduction levels between 20%24%.